Estimation of Potential Economic Benefits of Livestock Farming in Rural Madhya Pradesh - Agrawal, Aditi; Chaudhary, Udita; Raju, R. (Indian Journal of Extension Education, 2021)
The study was carried out using the secondary data on income, expenditure, productiveÂ assets and indebtedness of agricultural households in Madhya Pradesh collected from the Situation Assessment Survey (SAS) conducted by the National Sample Survey OfficeÂ (NSSO) in 70th round (2012-13). The household level data on various parameters was first extracted for Madhya Pradesh and brought into suitable form for carrying out analysis inÂ SPSS. Tabular analysis was employed to analyze the potential economic benefits of livestock farming. The findings revealed that marginal and small farmers earned only 26-27Â per cent of income of large farm households. Scheduled Caste and Scheduled Tribes who constitutes nearly 43.5 per cent of total farm households in Madhya Pradesh earns onlyÂ 33.8 and 33.4 per cent, respectively of the income of OBC farmers. Among the regions, farmers in the northern and central regions of the state earn the highest income while thoseÂ in the southern and vindhya regions earn the lowest income. in spite of farmersâ€™ high satisfaction in selling milk to cooperatives (72-75%), the share of cooperatives and government agencies was very less in procuring milk from farm households (3-5.5%) inÂ the state.